Geneza parafii rzymsko-katolickiej pod wezwaniem Matki Bożej Królowej Korony Polskiej w Baranowiczach - Żurek, Waldemar Witold (Archiwa, Biblioteki i Muzea Kościelne, 2015)
In 1928, society of the thriving borderland city of Baranowicze Poleskie launched a commendable initiative, the aim of which was to create another pastoral centre in that city for the local faithful of the Roman Rite. Those initiatives were made with great care for the spiritual good of the local faithful. The Executive Committee of the Church Construction appointed for that purpose in Baranowicze, then renamed the Citizens’ Committee of the Church Construction, did not take account of church law and practice in its structure. With a lay person being in charge, it did not receive approval of the ordinary of the Diocese of Pińsk, and thus efforts to build a church could not be carried out in accordance with expectations. It was not until 1934- when the parish priest and dean of Baranowicze, Rev. Jan Borysiuk, became the president of the Committee, that the relations with the diocesan ecclesiastical authority were normalised-that authority was the one which took decisions regarding the ongoing construction work in the new pastoral centre in Baranowicze. Long-term efforts on the creation of a new parish in that town resulted in erection- on 23 January 1937- the parish dedicated to Our Lady Queen of the Polish Crown and the appointment of its first parish priest Rev.Antoni Kohutnicki.